Effect Jamblang Stem Barks, Mangosteen Peel, and Cinnamon to Blood Sugar Levels - Thabed Tholib Baladraf (Newinera Publisher, 2021)
Diabetes mellitus ranks seventh as the most deadly disease with a prevalence of 1.9% and is dominated by type 2 diabetes mellitus with 95%. A solution is needed to overcome this problem, one of which is by utilizing jamblang stem barks, cinnamon, and mangosteen peel which are packaged in a popular product, namely steeping tea bags. This research aimed to determine the effect and potential biodiversity of extracts of jamblang stem barks, cinnamon and mangosteen peel as an antidiabetic drug in the form of infusion in rats induced by alloxan. This research used one-factor completely randomized design (CRD) with a linear model. Data were analyzed by One Way ANOVA and Post-hoc Tukey. The sample used was male mice aged 2-3 months with a body weight of ± 20 grams. The sample consisted of 25 individuals and divided into 5 groups. group I (control), group II (alloxan induction + jamblang stem barks extract, cinnamon, and mangosteen peel 1.35 grams / 200gBB), group III (alloxan induction + mangosteen peel 1.35 grams / 200gBB), group IV (alloxan induction + wood sweet 1.35 gram / 200gBB), group V (alloxan induction + jamblang stem barks 1.35 gram / 200gBB). Day 21, the amount of increase in blood sugar levels was observed and assessed based on the results of the tools used. The results showed that the infusion of jamblang stem barks, cinnamon and mangosteen peel had a significant effect on reducing blood sugar so that it could prevent type 2 diabetes mellitus.